The “demonization” of rainforest migrants, or: what conservation means to poor colonist farmers - Larson, A.M. (Springer, 2010)
Poor peasants – particularly rainforest colonists, who were heralded as pioneers until quite recently – are often blamed for the destruction of the world’s remaining tropical forests. This chapter uses a political ecology approach to examine rainforest colonization in the buffer zone of Nicaragua’s Indio-Maíz Reserve and to demonstrate that the “demonization” of peasant colonists is unjustified. It traces historical, cultural, and economic dynamics in rainforest migration and pasture conversion and examines the land use practices of recent colonists in the context of a dominant conservation discourse and a competing peasant-oriented counter-discourse. It attempts to understand the meanings of conservation to peasants themselves and argues that solutions will only be found when peasants’ viewpoints are fully taken into account – requiring integral, multiscale approaches.